DEVELOPMENT AND VALIDATION OF STABILITY INDICATING RP-UPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF TORSEMIDE AND SPIRANOLACTONE IN BULK AND PHARMACEUTICAL DOSAGE FORMS - Lalitha Repudi; M.Lakshmi Surekha (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Simple precise and accurate method was developed for the estimation of Torsemide and Spiranolactone. The mobile phase consisting 20% Buffer: 80%ACN. The column was used: Inertsil ODS 4.6*210mm, 5μ with flow rate 1ml/min using PDA detection at 235 nm. The estimation of Torsemide and Spiranolactone was done by RP-HPLC. The assay of Torsemide and Spiranolactone was performed with tablets and the % assay was found to be 99.65 and 100.07 which shows that the method is useful for routine analysis. The linearity of Torsemide and Spiranolactone was found to be linear with a correlation coefficient of 0.998 and 0.999, which shows that the method is capable of producing good sensitivity. The acceptance criteria of precision is RSD should be not more than 2.0% and the method show precision 0.1 and 0.7 for Torsemide and Spiranolactone which shows that the method is precise. The acceptance criteria of intermediate precision is RSD should be not more than 2.0% and the method show precision 0.2 and 0.2 for Torsemide and Spiranolactone which shows that the method is repeatable when performed in different days also. The accuracy limit is the percentage recovery should be in the range of 98.0% - 101.0%. The total recovery was found to be 99.69% and 99.39% for Torsemide and Spiranolactone. The validation of developed method shows that the accuracy is well within the limit, which shows that the method is capable of showing good accuracy and reproducibility. The acceptance criteria for LOD and LOQ are 3 and 10. The LOD and LOQ for Torsemide were found to be 2.98 and 10.00 and LOD and LOQ for Spironolactone were found to be 3.00 and 9.98.The robustness limit for mobile phase variation and flow rate variation are well within the limit, which shows that the method is having good system suitability and precision under given set of conditions.